4(3x-9)=-56

Simple and best practice solution for 4(3x-9)=-56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-9)=-56 equation:


Simplifying
4(3x + -9) = -56

Reorder the terms:
4(-9 + 3x) = -56
(-9 * 4 + 3x * 4) = -56
(-36 + 12x) = -56

Solving
-36 + 12x = -56

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '36' to each side of the equation.
-36 + 36 + 12x = -56 + 36

Combine like terms: -36 + 36 = 0
0 + 12x = -56 + 36
12x = -56 + 36

Combine like terms: -56 + 36 = -20
12x = -20

Divide each side by '12'.
x = -1.666666667

Simplifying
x = -1.666666667

See similar equations:

| (10b-6)-3(3b+4)=-3 | | -.5*32x^2+1000x+50=10 | | 2x^2+23x-6=0 | | 2x-4=-5x+2 | | 7x+6x+2+9=3x+5+9x | | 180=(x+96)+5x | | 13-6/5a=6 | | 5(4x+7)=-75 | | 1/2*4*3 | | 8x^2+2x=7x^2-2x+32 | | x+42=2x+1 | | 3+4=19 | | 10x-5=20-6 | | y=4w^2+450/x | | 8x-6=14-20 | | X^2-3x-60=0 | | 7/5+4/5=89/30+7/6x+5/6 | | x=24+4 | | -2(x+3)-2=-4(a-4) | | 3x-5x=6x+12 | | X=24y+4 | | 6(3x+3)=24 | | 1/2m+6=18 | | (8x-4)(9x+7)=0 | | 3/q=5/q+4 | | 1/12x^2-12=0 | | x^2-20+10x=180 | | 2x/6+14=x/4-7 | | 3/x+1=4/x-1 | | 4(x-6)=24 | | r=5d(60-t) | | r=1d(60-t) |

Equations solver categories